On Understanding Islam - Taufiq, Firmanda (Muslim Politics Review, 2023)
Understanding Islam: Position of Knowledge. Bryan S. Turner, Edinburgh: Edinburgh University Press, 2023. Paperback 210 pp. ISBN 978-1-4744-9874-6.